The Values, Acceptance, and Mindfulness Scale for Ice Hockey: A Psychometric Evaluation - Lundgren, Tobias; Reinebo, Gustaf; Löf, Per-Olov; Näslund, Markus; Svartvadet, Per; Parling, Thomas (Frontiers in Psychology, 2018)
Abstract There is an increased interest in mindfulness, acceptance and values based skills training interventions in sports but there is a lack of psychometrically evaluated instruments to investigate the processes adapted to sport populations. This paper describes the development and investigation of an instrument that measure acceptance, mindfulness and values for ice hockey players. Ice hockey players at elite and sub elite level (n=94) in Sweden participated in the study. The results reveal that the VAMS shows acceptable internal consistency (α=.76) and satisfactory validity. Furthermore, scores on the VAMS predicts ice hockey performance as measured by assists and team points. Future research is suggested to evaluate the sensitivity of the instrument for longitudinal research design studies. In conclusion, VAMS is a useful instrument for practitioners and researchers to increase the knowledge in how psychological processes such as acceptance; mindfulness and values influence performance among ice hockey players.